Gender differences in clinical characteristics of rheumatoid arthritis - Sakthiswary R,; Veshaaliini UR,; Syahrul Sazliyana S, (Penerbit UKM, 2023)
The most prevalent type of autoimmune inflammatory arthritis is rheumatoid arthritis (RA). Sex hormones are strongly associated in the pathogenesis and progression of RA. Hence, the core objective of this study was to compare the clinical features of RA among men and women. We consecutively recruited 23 men and 23 age-matched women with RA from our rheumatology clinic. Subjects were evaluated for their disease activities, radiographic joint damages and functional capacities. The above assessment was performed using DAS-28, Modified Sharp Score (MSS) and European League Against Rheumatism (EULAR) response criteria; respectively. The mean age for the male and female patients were 60.87 + 12.5 and 60.70 + 11.73, respectively. We found that the female subjects had significantly higher c-reactive protein (CRP) levels (p=0.05). The HAQ-DI(p<0.02) and MSS scores (p<0.001) of women were substantially higher than those of males. HAQ-DI and MSS remained to be independently associated with female gender in multivariate analysis, with p values of 0.017 and 0.014, respectively. The findings of this study suggested that in RA, compared to men, women had more severe joint damage and functional disability.